Basic bismuth oxyiodide, anion exchange membrane and electrolytic cell

By using basic bismuth iodide oxide material in anion exchange membrane and partially replacing iodine with hydroxide through hydrothermal reaction, the problems of AEM's stability and mechanical properties when improving conductivity are solved, and high conductivity and stability are achieved The combination of .

CN119118196AActive Publication Date: 2024-12-13TIANJIN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411296430.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-13
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

In the prior art, anion exchange membrane (AEM) is difficult to maintain chemical stability while improving electrical conductivity, and traditional methods tend to lead to excessive swelling of the membrane and degradation of mechanical properties.

Method used

The basic bismuth iodide oxide (BiOI1-x(OH)x) material is used as the key component of the anion exchange membrane, and is prepared by hydrothermal reaction method. The iodine in bismuth iodide oxide is partially replaced as hydroxide to form a high ionic conductivity and chemically stable membranes.

Benefits of technology

The ion conductivity and chemical stability of the anion exchange membrane are significantly improved, the electrolytic efficiency is improved, and excessive swelling of the membrane and mechanical properties are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118196A_ABST
    Figure CN119118196A_ABST
Patent Text Reader

Abstract

The invention discloses basic bismuth oxyiodide, an anion exchange membrane and an electrolytic bath, and belongs to the field of ion exchange membranes. The chemical formula of the basic bismuth oxyiodide is BiOI (1-x) (OH) x, and x is more than 0 and less than 1.0. The basic bismuth oxyiodide has an anion exchange characteristic, and shows high ionic conductivity and excellent stability after being used for preparing an anion exchange membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ion exchange membranes, and more specifically, relates to a basic bismuth iodide oxide material, an anion exchange membrane and a battery prepared using the basic bismuth iodide oxide material. Background Art

[0002] The increasing scarcity of fossil fuels has stimulated the demand for fast ion conductors, especially anion exchange membranes (AEMs), which are crucial for advancing energy conversion and storage devices such as water electrolysis, fuel cells, and flow batteries. Previous research has focused on developing high-conductivity AEMs based on polymer matrices rich in hydrophilic groups to improve the efficiency of devices such as energy conversion.

[0003] Based on this, the problems existing in the prior art are: traditional polymers obtain high conductivity by increasing the concentration of ions in AEM. However, this method usually causes excessive swelling of the membrane, resulting in poor mechanical properties of the membrane. In addition, polymer alkaline anion exchange membrane materials also face the problem of relatively poor chemical stability. The quaternary ammonium groups and the main chain in the polymer chain structure are easily affected by the strong alkaline nucleophilic reagent OH. - The attack leads to the degradation of the quaternary ammonium group and the main chain, the destruction of the membrane and the loss of conductivity.

[0004] Metal organic framework (MOF) materials can obtain relatively high ionic conductivity through molecular-level functional modification, which can increase the concentration of ions in AEM while maintaining excessive swelling and certain mechanical properties of the membrane. However, the functional groups in its structure will also be affected by the strong alkaline nucleophilic reagent OH - The attack of the film will degrade the film and affect its stability and conductivity. At the same time, its complex preparation process also limits its further commercial application.

[0005] Aluminum-magnesium layered hydroxide (LDH) can remain stable under certain alkali concentrations, but the aluminum element in it will react with OH for a long time or under some harsh working conditions. - The generation of aluminic acid leads to degradation, which affects the stability and conductivity of the membrane. At the same time, its conductivity is also relatively low (10 -2 S / cm) is difficult to form an excellent AEM.

[0006] Therefore, how to improve the chemical stability of AEM without losing conductivity is a difficult problem in the development of alkaline electrolyzer hydrogen production technology. Summary of the invention

[0007] 1. Problem to be solved

[0008] Based on this, the present invention provides a new material, basic bismuth iodide oxide, which is used to prepare anion exchange membrane;

[0009] Furthermore, the anion exchange membrane prepared using basic bismuth iodide oxide has significantly improved ion conductivity and high chemical stability.

[0010] Furthermore, the electrolytic cell comprising the anion exchange membrane prepared using basic bismuth iodide oxide has significantly improved electrolysis efficiency.

[0011] 2. Technical solution

[0012] The technical solution adopted by the present invention is as follows:

[0013] [Bismuth iodide basic]

[0014] The first aspect of the present invention provides a basic bismuth iodide oxide, the chemical formula of which is BiOI 1-x (OH) x , wherein 0<x<1.0. The compound has anion exchange properties.

[0015] The above-mentioned basic bismuth iodide oxide is based on bismuth iodide oxide, using OH - to I - Obtained by partial exchange.

[0016] As a preferred embodiment of the basic bismuth iodide oxide of any embodiment described in the first aspect of the present invention, x is 0.10 to 0.99; preferably, x is 0.3 to 0.99; more preferably, x is 0.3 to 0.7, or more preferably, x is 0.7 to 0.99.

[0017] It should be noted that the larger the value of x is, the better the anion exchange performance of the basic bismuth iodide oxide is. As a preferred embodiment of the basic bismuth iodide oxide of any embodiment described in the first aspect of the present invention, the density of hydroxide in the basic bismuth iodide oxide is 4.7 to 6.6 nm -2 Among them, the density of hydroxide ions is OH per unit area. - The number of .

[0018] The higher the density of hydroxide, that is, the larger the value of x, the better the anion exchange performance of basic bismuth iodide oxide.

[0019] As a preferred embodiment of the basic bismuth iodide oxide of any embodiment described in the first aspect of the present invention, the basic bismuth iodide oxide is a lamellar structure, and at least 80% or more of the lamellar structures have an aspect ratio of not less than 100, preferably an aspect ratio of not less than 200, more preferably an aspect ratio of not less than 400, more preferably an aspect ratio of not less than 500, and most preferably an aspect ratio of not less than 1000, calculated based on the number of lamellar structures with a lateral dimension greater than 50 nm in the AFM image. It is worth noting that, within the range that can be achieved in the prior art, the larger the aspect ratio of the basic bismuth iodide oxide, the more conducive it is to improving its anion exchange performance.

[0020] [Method for preparing basic bismuth iodide oxide]

[0021] The second aspect of the present invention provides a method for preparing basic bismuth iodide oxide according to any embodiment of the first aspect of the present invention, comprising the step of exfoliating bismuth iodide oxide crystals under hydrothermal conditions to obtain basic bismuth iodide oxide, wherein the chemical formula of the basic bismuth iodide oxide is BiOI 1-x (OH) x , where 0<x<1.0. Under hydrothermal conditions, OH in the solution - I on bismuth iodide crystals - Partial exchange is carried out to obtain basic bismuth iodide oxide.

[0022] It is worth noting that the bismuth oxyiodide crystals are of tetragonal system.

[0023] As a preferred method for preparing basic bismuth iodide oxide according to any embodiment of the second aspect of the present invention, the temperature of the hydrothermal condition is 120-200°C.

[0024] As a preferred method for preparing basic bismuth iodide oxide according to any embodiment of the second aspect of the present invention, the time of the hydrothermal reaction is 7 to 144 hours.

[0025] As a preferred method for preparing basic bismuth iodide oxide according to any embodiment of the second aspect of the present invention, in order to increase OH - to I - The exchange rate of BiOI was not lost without losing the aspect ratio of the bismuth iodide sheet structure. The bismuth iodide sheet was first exfoliated under hydrothermal conditions to obtain BiOI. 1-x1 (OH) x1 , wherein 0<x1<1.0; then the BiOI 1-x1 (OH) x1 Contact with alkali solution to obtain basic bismuth iodide BiOI 1-x2 (OH) x2 , where 0<x2≤1.0 and x1<x2.

[0026] Preferably, the BiOI 1-x1 (OH) x1 Contact with alkali solution includes BiOI 1-x1 (OH) x1 Soak in lye or spray with lye.

[0027] Typically, BiOI 1-x1 (OH) x1 The contact time with the alkali solution can be from a few hours to a few days or tens of days, for example, 1 hour to 30 days. Generally, the longer the contact time, the more OH - For the remaining I- The more exchanges there are.

[0028] [BiOI 1-x (OH) x ]

[0029] The third aspect of the present invention provides BiOI 1-x (OH) x , where x is 1.0; the BiOI 1-x (OH) x The sheet-like structure has an aspect ratio of not less than 100, preferably not less than 200, and more preferably not less than 400.

[0030] [Application of Bismuth Oxyiodide Basic]

[0031] The fourth aspect of the present invention provides the basic bismuth iodine oxide described in any embodiment of the first aspect of the present invention, or the basic bismuth iodine oxide prepared by the preparation method of the basic bismuth iodine oxide according to any embodiment of the second aspect of the present invention, or the BiOI described in the third aspect of the present invention. 1-x (OH) x , and its application in the preparation of anion exchange membranes. Experiments show that basic bismuth iodide is used in anion exchange membranes, and the anion exchange membranes have excellent anion exchange properties and chemical stability.

[0032] [Anion exchange membrane]

[0033] A fifth aspect of the present invention provides an anion exchange membrane, the anion exchange membrane comprising:

[0034] BiI 1-x (OH) x , where 0<x≤1.0; and

[0035] Auxiliary agent: Preferably, the auxiliary agent is selected from one or more of nanocellulose, polyvinyl alcohol, perfluorosulfonic acid polymer (Nafion), quaternized poly (aryl ether sulfone) (QAPES), quaternized poly (phenylene ether oxide) (QAPPO), and polybenzimidazole (PBI).

[0036] As a preferred anion exchange membrane of any embodiment described in the fifth aspect of the present invention, the mass percentage of basic bismuth iodide in the anion exchange membrane is 70-99%, preferably, the mass percentage of basic bismuth iodide in the anion exchange membrane is 75-90%.

[0037] As a preferred embodiment of the anion exchange membrane of any embodiment described in the fifth aspect of the present invention, the anion exchange membrane has a strength of not less than 80 mS cm at 90°C. -1Preferably, the anion exchange membrane has a conductivity of not less than 160mS cm at 90°C -1 conductivity.

[0038] As a preferred anion exchange membrane of any embodiment described in the fifth aspect of the present invention, the anion exchange membrane has an interlayer spacing of 0.80 to 0.95 nm, preferably 0.80 to 0.90 nm, and the interlayer spacing is calculated based on the XRD diffraction pattern of the anion exchange membrane.

[0039] [Electrolyzer]

[0040] The sixth aspect of the present invention provides an electrolytic cell, comprising the basic bismuth iodine oxide according to any one embodiment of the first aspect of the present invention, or the basic bismuth iodine oxide prepared by the preparation method of any one embodiment of the second aspect of the present invention, or the BiOI according to the third aspect of the present invention. 1-x (OH) x , or the anion exchange membrane described in any one of the embodiments of the fifth aspect of the present invention.

[0041] 3. Beneficial effects

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] (1) The present invention provides a new material, basic bismuth iodide oxide, in which part of the iodine is replaced by hydroxide. The basic bismuth iodide oxide has anion exchange properties and exhibits high ion conductivity and excellent stability after being used to prepare anion exchange membranes.

[0044] (2) Further, basic bismuth iodide (BiOI 1-x (OH) x ), x is 0.10 to 0.99, in particular, x is 0.30 to 0.70. When the basic bismuth iodide oxide contacts with a base, the value of x increases, for example, to a value of x of 0.70 to 0.99. As the value of x increases, after the anion exchange membrane is prepared, the ionic conductivity increases.

[0045] (3) The present invention adopts basic bismuth iodide (BiOI 1-x (OH) x ) to prepare anion exchange membrane having significantly improved ionic conductivity.

[0046] (4) The present invention adopts a hydrothermal reaction method for the first time to strip bismuth iodide from bismuth iodide crystal materials. During the reaction, basic bismuth iodide is unexpectedly obtained. After the basic bismuth iodide is used to prepare an anion exchange membrane, it exhibits high ionic conductivity. Furthermore, the basic bismuth iodide obtained by hydrothermal reaction is contacted with an alkali solution to obtain basic bismuth iodide with an increased value of x. After the basic bismuth iodide is used to prepare an anion exchange membrane, it has improved ionic conductivity.

[0047] (5) The present invention comprises using basic bismuth iodide (BiOI 1-x (OH) x ) has a significantly improved electrolysis efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 Characterization of BiOI crystals prepared by hydrothermal reaction. (a) BiOI crystal image under optical microscope. (b) Scanning electron microscope (SEM) image. (c) High-resolution transmission electron microscope (HRTEM) image. (d) Transmission electron microscope element mapping (TEM element mapping). (e) X-ray diffraction (XRD) pattern. (f) Crystal structure of BiOI. Scale bars: (a) 10 μm; (b) 10 μm; (c) 2 nm, 5 nm -1 ; (d) 1 μm. The square shape of the BiOI crystal matches its tetragonal structure, which can also be confirmed by the (001), (002), (003), and (004) crystal planes in the XRD results.

[0049] Figure 2Preparation process of basic bismuth iodide nanosheets and basic bismuth iodide membranes with further base exchange. (a) Schematic diagram of the preparation process of basic bismuth iodide (x = 0.36) nanosheets, including two steps of hydrothermal intercalation and microfluidization, aimed at preparing basic bismuth iodide (x = 0.36) nanosheets from BiOI crystals. (b) Atomic force microscopy (AFM) images of basic bismuth iodide (x = 0.36) nanosheets synthesized during hydrothermal exfoliation at 160 °C and 24 h. The height profile indicated by the white line shows that the thickness is 3.89, 3.97 and 3.81 nm, respectively. (c) The lateral size distribution and thickness distribution of basic bismuth iodide (x = 0.36) synthesized during hydrothermal exfoliation at 160 °C and 24 h. (d) UV absorption intensity of basic bismuth iodide supernatant prepared at 160 °C with different hydrothermal times at 226 nm and its corresponding atomic ratio of Bi and I in basic bismuth iodide nanosheets. (e) Cross-sectional scanning electron microscopy (SEM) image of the basic bismuth iodide (x = 0.36) film synthesized during the hydrothermal exfoliation process at 160 ° C and 24 h. The inset shows the flexibility of the basic bismuth iodide (x = 0.36) film. (f) OH exchange ratios obtained by EDS measurement of basic bismuth iodide with different immersion times in 1 M NaOH aqueous solution. The inset shows a schematic diagram of the exchange of basic bismuth iodide with different OH ratios. (g) X-ray diffraction (XRD) spectra of basic bismuth iodide with different OH exchange times. The peaks at 9.6° and 10.8° are called peak I and peak II, respectively. Scale bars: (b) 5 μm, (e) 1 cm (inset) and 2 μm.

[0050] Figure 3 Preparation and characterization of basic bismuth oxyiodide nanosheets. (a) Schematic diagram of the preparation of basic bismuth oxyiodide nanosheets. The synthesized bulk BiOI crystals were first hydrolyzed in water and then subjected to microfluidic homogenization to obtain basic bismuth oxyiodide (x = 0.36) nanosheets. (b) Photographs of basic bismuth oxyiodide (x = 0.36) nanosheets suspended in an ethanol-water mixture. (c) Lateral dimensions of basic bismuth oxyiodide nanosheets prepared with different hydrolysis times. (d) High-resolution transmission electron microscopy (HRTEM) images showing the (001) crystal plane of basic bismuth oxyiodide (x = 0.36) nanosheets with a (110) lattice spacing of 0.282 nm. (e) Transmission electron microscopy (TEM) images and elemental mapping images of basic bismuth oxyiodide (x = 0.36) nanosheets. (f) Maximum lateral dimensions and minimum thickness of two-dimensional bismuth oxyhalides prepared by various methods. Our additive-free, hydrothermal exfoliation method is highly competitive among both top-down and bottom-up methods. Scale bars: (d) 2 nm, 5 nm -1 ; (e) 2 μm.

[0051] Figure 4Effect of hydrolysis time on the formation of basic bismuth iodide nanosheets: (a) UV absorption intensity of the centrifugal supernatant after basic bismuth iodide nanosheets prepared at different hydrolysis times. (b) XPS spectra of basic bismuth iodide nanosheets prepared at different hydrolysis times. (c) O Bulk (oxygen in the crystal) and O v (d) The peak area ratio of O in basic iodine bismuth oxide nanosheets prepared at different hydrolysis times Bulk and O O-H (hydroxyl oxygen) peak area ratio.

[0052] Figure 5 Effect of hydrolysis time on the formation of basic bismuth iodide nanosheets: (a) Schematic diagram of the formation process of basic bismuth iodide nanosheets under different hydrolysis times. (bf) Scanning electron microscope (SEM) images of BiOI nanosheets supported on AAO (alumina filter membrane) substrate. Scale bar: 2 μm. (gk) Corresponding lateral size distribution of basic bismuth iodide nanosheets.

[0053] Figure 6 Effect of hydrolysis temperature on the formation of basic iodine bismuth oxide nanosheets: (a, b) UV absorption intensity of the supernatant of basic iodine bismuth oxide nanosheets after 13 hours of hydrolysis at different hydrolysis temperatures and the atomic ratio of Bi and I in basic iodine bismuth oxide nanosheets. (c) XPS spectra of basic iodine bismuth oxide nanosheets prepared at different hydrolysis temperatures. (d) O Bulk (oxygen in the crystal) and O v (oxygen vacancy) peak area ratio.

[0054] Figure 7 .Anion transport in basic bismuth iodide oxide membrane: (a) OH - Schematic diagram of transport in bismuth iodide oxide films at different hydroxide substitution ratios. (b) BiOI 1-x (OH) x (x=0.97) Ionic conductivity of the membrane. (c) BiOI under different humidity 1-x (OH) x (d) Simulation calculation: Ionic conductivity of BiOI 0.67 (OH) 0.33 (black line), BiOI 0.44 (OH) 0.56 (blue line) and OH in BiOI0(OH)1 (orange line) -The mean square deviation displacement (MSD) of the BiOI 0.67 (OH) 0.33 、BiOI 0.44 (OH) 0.56 (f) The relationship between ionic conductivity and IEC of different materials. (g) Hardness and elastic modulus of basic bismuth iodide membrane (x = 0.36) and commercial FAA HEM. (h) Radar chart comparing the conductivity, IEC, gas permeability, hardness, swelling ratio and other properties of basic bismuth iodide membrane (x = 0.36) and commercial FAA.

[0055] Figure 8 . Water electrolysis performance of bismuth iodide hydroxide (x = 0.97) hydroxide ion exchange membrane. (a) Schematic diagram of the experimental device. (b) Water electrolysis polarization curve assembled with bismuth iodide hydroxide (x = 0.97) membrane, FAA-PK-130 and PPS (electrolyte: 15% KOH, 60°C). (c) EIS of each membrane material before stability test. (d) Electrochemical performance of bismuth iodide hydroxide (x = 0.97) hydroxide ion exchange membrane at 1000 mA cm -2 The stability test of the membrane in water electrolysis under the conditions of (electrolyte: 15% KOH, 60°C). (e) Comparison of the stability of the basic bismuth iodide (x=0.97) membrane with other membrane materials. Fig. 9 Performance of basic bismuth iodide (x = 0.97) membrane in water electrolysis: (a) Polarization curves of basic bismuth iodide (x = 0.97) membrane at different temperatures in 3M KOH electrolyte. (b) Polarization curves of basic bismuth iodide (x = 0.97) membrane in different concentrations of circulating KOH electrolyte at 60°C. (c) Polarization curves of basic bismuth iodide (x = 0.97) membrane at 1000mA cm -2 (d) Electrochemical impedance spectroscopy (EIS) of the membrane before and after the stability test. (e) O2 purity at different test current densities at 60°C in 3M KOH electrolyte, measured by a hydrogen sensor. (f) X-ray diffraction (XRD) of basic bismuth iodide oxide (x=0.97) membrane before and after the electrolysis water stability test. The test conditions were 120 hours, the electrolyte was 3M KOH, and the temperature was 60°C. The structure of basic bismuth iodide oxide (x=0.97) can be displayed by the (001) peak at 10.8°. The existence of this peak proves that the layered structure of basic bismuth iodide oxide (x=0.97) has not been destroyed, and no structural changes were observed after the electrolysis water test, proving its excellent stability. DETAILED DESCRIPTION

[0056] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs; the term "and / or" used herein includes any and all combinations of one or more of the associated listed items.

[0057] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0058] As used herein, the term "about" is used to provide flexibility and imprecision associated with a given term, measurement or value. The degree of flexibility for a particular variable can be easily determined by one skilled in the art.

[0059] Concentration, amount and other numerical data can be presented in range format herein.It should be understood that such range format is only used for convenience and simplicity, and should be flexibly interpreted as not only including the numerical value clearly described as range limit, but also including all single numerical values ​​or sub-ranges contained in the range, just as each numerical value and sub-range are clearly described.For example, the numerical range of about 1 to about 4.5 should be interpreted as not only including the limit value of 1 to about 4.5 clearly described, but also including single numerals (such as 2,3,4) and sub-ranges (such as 1 to 3,2 to 4, etc.).The same principle is applicable to the scope of only narrating a numerical value, such as "less than about 4.5", which should be interpreted as including all the above-mentioned values ​​and ranges.In addition, no matter how the breadth of the described range or feature is, this explanation should be applicable.

[0060] The present invention is further described below in conjunction with specific embodiments.

[0061] In this study, a HEM membrane based on bismuth iodide nanosheets was developed. By replacing iodide with hydroxide, the content of interlayer short hydrogen bonds (SHB) was increased, providing a fast Grotthuss-type anion transport channel in confined water, resulting in a significant increase in ionic conductivity. With the promotion of SHB, BiOI HEM with full or partial replacement of hydroxide was applied to membrane electrode assemblies, showing efficient and durable alkaline water electrolysis hydrogen production performance.

[0062] Materials Characterization and Testing Technology

[0063] BiI 1-x (OH) x The surface structure and morphology of BiOI were characterized using a Carl Zeiss Merlin high-resolution field emission scanning electron microscope (FE-SEM) at 5.0 kV. 1-x (OH) xThe thickness of the nanosheets was measured by AFM (BrukerDimension ICON-PT). UV-visible spectroscopy was performed on a TU-1901 (Beijing Puxi Instrument Co., Ltd.) spectrophotometer. TEM was performed using a Thermo Scientific Talos F200X electron microscope operated at 300 kV. The HyPix-400 MF 2D hybrid pixel array detector (HPAD) and Cu K α X-ray source (wavelength XRD patterns were obtained using a Rigaku benchtop X-ray diffractometer with Bragg-Brentano geometry, operating at 40 kV and 15 mA. X-ray photoelectron spectroscopy (XPS) was used to analyze the surface chemical state using an Al K α The X-ray radiation was carried out on an AXIS Ultra DLD instrument. Low-field nuclear magnetic resonance (LF-NMR) measurements were performed on a 20 MHz NMR analyzer (A NMI20-Analyst NMR analyzer, Suzhou Niumag Analytical Instrument Co., Ltd., China). About 5 mg of the fully hydrated film was placed in a glass tube, and the NMR probe was inserted into the glass tube during the test. T2 was measured using a Carre-Purcelle-Meiboome-Gill (CPMG) sequence. Infrared spectroscopy (FT-IR) was performed on an infrared imaging microscope (iN10 MX infrared imaging microscope, Thermo Scientific TM ,Nicolet TM ), using attenuated total reflection (ATR) mode in air environment. The nanoindentation test was performed at room temperature on a nanoindentation analyzer (NHT2 Nanoindentation Analyzer, Anton Paar Instruments, Austria) in pressure control mode using a triangular pyramid probe. The maximum pressure applied was 10 μN, and the results were obtained by repeating five times.

[0064] Commercial hydroxide ion exchange membrane (FAA-PK-130) was purchased from

[0065] Commercial hydroxide ion exchange membrane FA-500 (polyphenylene sulfide, PPS) was purchased from Hangzhou Huamo Co., Ltd. BiOI 1-x (OH) x Middle I - Determination of content

[0066] BiI 1-x (OH) x Middle I -The content of was measured by EDS of SEM, specifically, the characterization was carried out at 15.0 kV using the high-efficiency fast element energy spectrum (EDS) accessory of Carl Zeiss Merlin high-resolution field emission scanning electron microscope (FE-SEM).

[0067] Swelling rate test

[0068] The membrane expansion ratio (SR) is calculated by the wet state (d wet , in hydroxide form) and dry state (d dry ,inhydroxideform)BiOI 1-x (OH) x The film thickness difference is determined and calculated according to the following equation:

[0069]

[0070] Ion Exchange Capacity (IEC) Test

[0071] BiI 1-x (OH) x The ion exchange capacity (IEC) of the membrane was determined by Mohr titration. The dried BiOI membrane (in hydroxide form) was immersed in 50 ml of 0.5 M Na2SO4 standard solution at 25 °C for 4 hours, repeated three times. These solutions were then titrated with standardized HCl solution using a mixed solution of methyl red and methylene blue as an indicator. IEC was calculated according to the following equation:

[0072]

[0073] Among them, c HCl is the concentration of HCl solution; V HCl is the volume of HCl solution; m BiOI is the dry weight of BiOI film (g). Conductivity test

[0074] Before the ionic conductivity test, the membrane was treated in 1M NaOH aqueous solution for 1 hour, and then the adsorbed hydroxide ions were thoroughly washed with deionized water. Electrochemical impedance spectroscopy (EIS) was performed using two platinum electrodes in the range of 0.1 Hz to 1 MHz using MFIA LCR (Zurich Instrument Inc.). The x-axis intercept at high frequency was regarded as the resistance of the sample. The ionic conductivity (σ) was calculated according to the following equation:

[0075]

[0076] Where R, S and L are the resistance of the sample, the effective area and the thickness of the film respectively.

[0077] Electrolyzed water test

[0078] The membrane electrode assembly (MEA) was prepared by sandwiching a hydroxyl ion exchange membrane with an active area of ​​1 cm2 between the anode and cathode. The anode and cathode preparation process involved spraying the catalyst ink (anode: IrO2 / FAA-3, cathode: Pt / C / FAA-3) on the membrane with a loading content of 6 mg / cm2 and 3 mg / cm2, respectively. KOH solution was used as the electrolyte and flowed to the cathode and anode at a flow rate of 5 ml / min. The temperature was maintained at a specified value and monitored by thermocouples. The cell was maintained at 1 volt to detect holes or other short circuits in the MEA in the cell (the electrolysis current should decay to zero at a voltage less than 1.23 volts, and the short circuit current will persist if it exists). Subsequently, the cell voltage was adjusted to 1.5 volts and maintained for 15 minutes to reach a steady state. Polarization curves were obtained by recording the current density in the voltage range of 1.4 to 2.0 volts. Stability tests were performed at a constant current density and the corresponding voltage data were collected.

[0079] Hydrogen permeability test

[0080] The hydrogen permeation performance was obtained by the alkaline water electrolysis device mentioned above. Under the operating conditions, the hydrogen volume was obtained by the water displacement method. Hydrogen content in generated oxygen It is determined by a hydrogen sensor (JEC-H2 hydrogen sensor from Jingxun Changtong Instrument Co., Ltd., China). Hydrogen permeation (P) is calculated by the following equation:

[0081]

[0082] Where l is BiOI 1-x (OH) x is the thickness of the membrane, Δp is the hydrogen pressure difference across the membrane, S is the effective area, and t is the time.

[0083] Example

[0084] 1. Synthesis of base exchange BiOI (basic bismuth oxide iodide) membrane

[0085] (1) Preparation of bismuth iodide crystals

[0086] Ethanol (50 mL), bismuth nitrate pentahydrate (0.2 mmol) and sodium iodide (0.4 mmol) were mixed, stirred thoroughly in a 100 mL hydrothermal reactor, and heated to 160 ° C for 24 hours. The obtained product was reddish brown BiOI crystals. The crystals were characterized as follows Figure 1 The product was washed with water and ethanol and dried at 60 °C for 12 h with a yield of 94.5%.

[0087] (2) Preparation of basic bismuth iodide nanosheets

[0088] like Figure 2 As shown in a, the top-down exfoliation of BiOI nanosheets is first achieved by subcritical water intercalation and microfluidic homogenization technology-assisted exfoliation. Figure 1 b) as raw materials, and successfully exfoliated and obtained basic iodine bismuth oxide nanosheets through subcritical water (SCW) intercalation under hydrothermal conditions. Compared with previous studies, the exfoliation method of the present invention does not require the use of hazardous chemicals, such as butyl lithium. The specific steps are as follows:

[0089] SCW intercalation: BiOI crystals (50 mg) were mixed with ultrapure water (50 mL) and heated to 120-200 ° C in a 100 mL hydrothermal reactor with a protective atmosphere of N2 for 7-144 hours. In this embodiment, in order to reduce the side reaction of XY direction degradation during the intercalation of SCW, the hydrothermal reaction conditions of the intercalation process were optimized to 160 ° C and 24 hours ( Figure 2 d).

[0090] Exfoliation (microfluidic homogenization technology): After cooling to room temperature, the mixture was transferred to a microfluidic homogenizer (model: NLM100, manufacturer: Nissin) and processed at a pressure of 800 bar for 50 cycles. Subsequently, the mixture was centrifuged (1000 rpm, 10 minutes) to obtain a supernatant (about 0.40 mg / mL); the supernatant was centrifuged at 14000 rpm for 10 minutes, and the precipitate was a basic iodine bismuth oxide nanosheet with an appropriate aspect ratio. Calculated by the number of sheet structures with a lateral size greater than 50 nm in the AFM image, more than 80% of the basic iodine bismuth oxide nanosheets had an aspect ratio greater than 100. The basic iodine bismuth oxide nanosheets are characterized as follows: Figure 2 As shown in bc.

[0091] EDS measured that 36% of the iodine in the bismuth oxide iodide crystals was replaced by hydroxide ions in water, that is, the basic bismuth oxide iodide obtained was BiOI 1-x (OH) x , where x is 0.36.

[0092] Under the same conditions, only BiOI crystals successfully obtained basic bismuth iodide under hydrothermal conditions, while BiOCl and BiOBr failed to intercalate successfully under the same conditions and no OH-substituted products could be obtained.

[0093] In the above method, if Figure 3As shown in a, after SCW intercalation, the intercalated BiOI nanosheets (basic iodine bismuth oxide nanosheets) were non-destructively peeled off using microfluidic homogenization technology and configured into a basic iodine bismuth oxide nanosheet dispersion with a solid concentration of 0.4±0.04 g / L ( Figure 3 b). The average thickness and average lateral size of the 2D basic bismuth iodide nanosheets (x=0.36) are 3.8±0.49nm and 1.7±1.01μm, respectively. Figure 3 c), the average aspect ratio is about 450. Compared with previous studies (BiOX series materials), the aspect ratio has been significantly improved ( Figure 3 f). Figure 3 d shows a high-resolution transmission electron microscopy (HRTEM) image of basic bismuth iodide oxide nanosheets, showing the (001) crystal plane of basic bismuth iodide oxide nanosheets and the (110) lattice distance of 0.282 nm. Figure 3 e shows that there are Bi, O, and I elements on the basic bismuth iodide nanosheets.

[0094] In summary, the present invention successfully synthesized well-dispersed basic bismuth iodide nanosheets with high aspect ratio through SCW intercalation and microfluidic homogenization technology, and prepared to use it to construct an adjustable 2D nanochannel-basic bismuth iodide membrane.

[0095] In some embodiments, the effect of different hydrolysis times on the formation of basic bismuth iodide oxide nanosheets under the same conditions (160° C.) was also studied. Figure 4 and Figure 5 shown.

[0096] In some embodiments, the effects of different hydrolysis temperatures on the formation of basic bismuth iodide oxide nanosheets under the same conditions and the same hydrolysis time (13 h) were also studied. Figure 6 shown.

[0097] (2) Preparation of Bismuth Hydroxyiodide (x = 0.36) Film

[0098] Furthermore, the basic bismuth iodide oxydispersed solution (x=0.36) obtained in (1) was vacuum filtered to prepare a semi-transparent film having a certain degree of flexibility, such as Figure 2 e illustration, specifically:

[0099] In order to enhance the mechanical strength of the basic bismuth iodide film, about 20 wt% CNF (CNF dispersion 0.5 mg / mL) was added in this embodiment and mixed with the exfoliated basic bismuth iodide (x=0.36) dispersion (0.4±0.04 g / L, 10 mL), and a basic bismuth iodide (x=0.36) film (thickness: 4.99 μm) was obtained by vacuum filtration. The basic bismuth iodide nanosheets in the film formed long-range ordered 2D channels ( Figure 2e), and the density of hydroxide in the basic bismuth iodide film is 2.30 nm -2 , x is 0.36.

[0100] (3) Alkali exchange treatment of basic bismuth iodide oxide membrane

[0101] BiOI 0.64 (OH) 0.36 The membrane was treated with alkali (NaOH, 1M) exchange, and the density of hydroxide ions in the membrane gradually increased:

[0102] BiI 0.35 (OH) 0.65 Membrane preparation: After 5 days of base exchange treatment, the density of hydroxide in the basic bismuth iodide oxide membrane is 4.35nm -2 , x is 0.65;

[0103] BiI 0.17 (OH) 0.83 Membrane preparation: After 10 days of base exchange treatment, the density of hydroxide in the basic bismuth iodide oxide membrane is 5.56nm -2 , x is 0.83;

[0104] BiI 0.03 (OH) 0.97 Membrane preparation: After 20 days of alkaline exchange treatment, the density of hydroxide in the basic bismuth iodide oxide membrane can be increased to 6.08nm -2 , x is 0.97 (such as Figure 2 f);

[0105] The increase in hydroxide density can be used to adjust the hydrophilicity in the anion transport channel. In the basic iodine oxide membranes obtained after different alkaline exchange treatments (0-20 days), the 2D interlayer channel spacing of the membrane that has not been treated with alkaline exchange (x is 0.36) is 0.91nm (peak I). With the increase in the amount of hydroxide exchange, the interlayer spacing of the basic iodine oxide membrane treated with alkaline exchange for 20 days (x is 0.36, and x is 0.97 after 20 days) is reduced to 0.82nm (peak II). Therefore, the OH in basic iodine oxide can be used to regulate the hydrophilicity of the anion transport channel. - Content-controlled nanochannel spacing ( Figure 2 g). Therefore, the 2D basic bismuth iodide membrane can provide a 2D nanochannel with a controllable confined space and distributed hydrophilic groups for subsequent anion conduction.

[0106] 2. Anion Transport in Basic Bismuth Oxyiodide Membranes

[0107] The basic bismuth iodide film has adjustable interlayer hydrogen bonds. Experiments show that as the degree of alkali exchange deepens, the conductivity of the basic bismuth iodide film increases. For example, the basic bismuth iodide films with x = 0.36, x = 0.65, x = 0.83, and x = 0.97 prepared in [I. Synthesis of alkali exchange BiOI (basic bismuth iodide) membranes], as the x value increases, the SHB network in the confined water expands (see Figure 7 a) The conductivity of the basic bismuth iodide film at 90°C increased from 84.7 mS cm -1 (x = 0.36) rapidly increases to 168 mS cm -1 (x=0.97)(See Figure 7 b), which is higher than most reported polymer HEMs, such as o-PDQA (106 mS cm -1 、Tec-PBI-60(131.8mS cm -1 )、QAPPT(137mS cm -1 ), showing similarity to commercial PEM (e.g. 83mS cm -1 ) comparable performance.

[0108] In addition, the bismuth iodide basic oxide film exhibited humidity-dependent ionic conductivity behavior, indicating the key effect of SHB in nanoconfined water (see Figure 7 c) However, under 50RH%, BiOI 1-x (OH) x The ionic conductivity of (x = 0.97) still reaches 4.24 mS cm -1 , which is three orders of magnitude higher than FAA (a typical commercial HEM). To study the ion selectivity of the basic bismuth iodide membrane, we used the concentration diffusion method to test it. 0.64 (OH) 0.36 The open circuit voltage (V0) of OH is +54.9 mV, indicating that the 2D channel is positively charged. According to the Nernst equation, - The transmission number is 0.77 ( Figure 7 d and e), indicating that the ionic conductivity of layered basic bismuth iodide is mainly attributed to OH - Therefore, basic bismuth iodide membrane has the potential to become a HEM.

[0109] Interestingly, the ion exchange capacity (IEC) of our bismuth iodide (x = 0.36) membrane is only 8.5 × 10 - 4 mmol / g, significantly lower than those polymer ion exchange membranes with similar or lower conductivity (see Figure 7f). In most previous studies, the conductivity of the -1 Above this, IEC is usually required to be higher than 2 mmol / g, so people try to increase the number of modified charged functional groups. In this process, swelling and degradation of functional groups inevitably occur, resulting in a decrease in ionic conductivity and other important physical properties (e.g., mechanical strength and gas permeability). In terms of anti-swelling performance, the basic bismuth iodide oxide membrane (x = 0.36) is 24.7% higher than the commercial FAA, and the elastic modulus is 140% higher (see Figure 7 g and h). In addition, under experimental conditions, the H2 permeability of the basic bismuth iodide membrane (x = 0.36) was 0.244 Barrer, which was 6.9% lower than that of FAA. Therefore, it is speculated that the short hydrogen bond network formed by the interaction in the confined space and the interface can give HEM a superior conductivity that is independent of IEC, thereby indirectly improving the mechanical and chemical stability of HEM (see Figure 7 h).

[0110] 3. Application of Bismuth Oxide Iodide Membrane in Electrolysis of Recycled Water

[0111] To demonstrate the potential of bismuth iodide basic membrane as a high-conductivity HEM, we applied bismuth iodide basic membrane (x = 0.97) to alkaline membrane electrolysis of water (see Figure 8 a), and commercial hydroxide ion exchange membranes (FAA-PK-130) and FA-500 (polyphenylene sulfide, PPS) were used for comparison. Based on the analysis of the polarization curve data at 60°C, the membrane electrode (MEA) made of bismuth iodide oxide (x = 0.97) with the highest conductivity had a current density of 1760 mA cm at 2.0 V. -2 , which is about 1200mA cm higher than that of FAA-PK-130 and PPS -2 (See Figure 8 b) After adjusting the experimental temperature to 80 °C, the current density can be further increased to 1986 mA cm -2 (See Fig. 9 This excellent water electrolysis performance is mainly attributed to the extremely high hydroxide ion conductivity of the basic bismuth iodide membrane, which is manifested in the low ohmic resistance (Rohm) and interfacial charge transfer resistance (Rct) (see Figure 8 c and 9c, d). In addition, basic bismuth oxyiodide (x = 0.97) HEM was tested at 1000 mA cm -2 It can run for more than 5 days with a voltage loss of only 96μV h -1 , which is higher than FAA-PK-130 and PPS (1049μV h -1 and 2967μV h -1) 31 and 11 times lower (see Figure 8 d and Table 1), high current density and alkali concentration usually accelerate the degradation of HEM, however, the voltage loss rate of the basic bismuth iodide film (x = 0.97) is even lower than that of other reported HEMs, especially the highly conductive films (see Figure 8 e), confirming its excellent durability under water electrolysis operating conditions. In addition, the Rohm and Rct of basic bismuth iodide (x = 0.97) MEA decreased after the experiment (see Fig. 9 c and d), indicating that the in situ hydroxyl substitution further activated the ionic conductivity of the basic bismuth oxyiodide HEM. In contrast, the resistance of the commercial membrane MEA increased after the experiment, indicating that it had degraded (see Fig. 9 c). In addition, after 120 hours of continuous operation, no obvious structural degradation of basic bismuth iodide (x = 0.97) HEM was observed by XRD characterization (see Fig. 9 f), so that the MEA of the present invention exhibits excellent stability. Due to its layered structure and sub-nano channels, basic bismuth iodide (x = 0.97) exhibits a lower H2 permeability, as mentioned above, only 0.244 Barrer, which is four orders of magnitude lower than PPS (1095.7 Barrer) (see Fig. 9 e). Therefore, compared with other reported HEMs, the basic bismuth iodide HEM of the present invention exhibits excellent performance in water electrolysis, with higher current density, lower voltage loss and good stability.

[0112] Table 1 Water electrolysis performance of different AEMs

[0113]

[0114] In this work, we developed a HEM based on 2D bismuth iodide suboxide. We used SCW (supercritical water) intercalation and microfluidic homogenous exfoliation techniques to prepare high aspect ratio bismuth iodide suboxide nanosheets for constructing long-range ordered nanoconfined channels. The active groups on the inner wall of the channel can be replaced by hydrophilic groups, providing a facile way to regulate interlayer hydrogen bonds. As iodine is replaced by hydroxyl groups, the short hydrogen bond (SHB) network can expand in the 2D nanochannels, creating more Grotthuss-type diffusion paths to promote fast ion transport. Thanks to the SHB network in confined water, the conductivity of the hydroxide of the bismuth iodide suboxide (x = 0.97) layered structure is improved to 168 mS cm at 90 °C. -1, resulting in excellent performance of MEAs based on basic bismuth oxyiodide in alkaline water electrolysis. In addition, the fast ion transport due to the SHB network does not require an increase in ion exchange capacity (IEC), thus avoiding the side effects of higher IEC, such as reduced mechanical strength, decreased chemical stability, and reduced gas barrier properties. Therefore, our work will open up new avenues for HEMs in sustainable energy conversion.

[0115] The above content is a schematic description of the present invention and its implementation methods, which is not restrictive. What is shown in the embodiment is only one of the implementation methods of the present invention, and the actual implementation method is not limited thereto. Therefore, if a person of ordinary skill in the art is inspired by it and designs implementation methods and embodiments similar to the technical solution without creative design without departing from the purpose of the invention, they should all fall within the scope of protection of the present invention.

Claims

1. Basic bismuth iodide oxide, the basic bismuth iodide oxide chemical formula is BiOI 1-x (OH) x ,in, 0<x<1.0。 2. The basic bismuth oxyiodide according to claim 1, wherein The value of x is 0.10 to 0.99; preferably, the value of x is 0.30 to 0.99; more preferably, the value of x is 0.30 to 0.70, or more preferably, the value of x is 0.70 to 0.

99.

3. The basic bismuth iodide according to claim 2, characterized in that The density of hydroxide in the basic bismuth iodide oxide is 4.7 to 6.6 nm. -2 .

4. The basic bismuth oxyiodide according to any one of claims 1 to 3, characterized in that The basic bismuth iodide oxide is a lamellar structure. Calculated based on the number of lamellar structures with a lateral dimension greater than 50 nm in the AFM image, at least 80% of the lamellar structures have an aspect ratio of not less than 100, preferably not less than 200, and more preferably not less than 400.

5. The method for preparing basic bismuth iodide according to any one of claims 1 to 4, characterized in that: The method comprises the steps of exfoliating bismuth iodide crystals under hydrothermal conditions to obtain basic bismuth iodide, wherein the chemical formula of the basic bismuth iodide is BiOI 1-x1 (OH) x1 , wherein 0<x1<1.0; preferably, the BiOI 1-x1 (OH) x1 Contact with alkali solution to obtain basic bismuth iodide BiOI 1-x2 (OH) x2 , where 0<x2≤1.0 and x1<x2. 6.BiOI 1-x (OH) x ,in, x takes a value of 1.0; the BiOI 1-x (OH) x The sheet-like structure has an aspect ratio of not less than 100, preferably not less than 200, and more preferably not less than 400.

7. The basic bismuth iodide oxide according to any one of claims 1 to 4, or the basic bismuth iodide oxide prepared by the preparation method of claim 5, or the BiOI according to claim 6 1-x (OH) x , application in the preparation of anion exchange membranes.

8. Anion exchange membrane, characterized in that The anion exchange membrane comprises: BiI 1-x (OH) x , where 0<x≤1.0; and Auxiliary agent; preferably, the auxiliary agent is selected from one or more of nanocellulose, polyvinyl alcohol, perfluorosulfonic acid polymer, quaternized poly(aryl ether sulfone), quaternized poly(phenylene oxide), and polybenzimidazole; Preferably, the anion exchange membrane BiOI 1-x (OH) x The mass percentage is 70-99%.

9. The anion exchange membrane according to claim 8, characterized in that The anion exchange membrane has a temperature of not less than 80 mS cm at 90°C. -1 Preferably, the anion exchange membrane has a conductivity of not less than 160mS cm at 90°C -1 The conductivity of Alternatively, the anion exchange membrane has an interlayer spacing of 0.80 to 0.95 nm, and the interlayer spacing is calculated based on an XRD diffraction pattern of the anion exchange membrane.

10. An electrolytic cell, characterized in that The bismuth iodide basic compound comprises any one of claims 1 to 4, or the bismuth iodide basic compound prepared by the preparation method of claim 5, or the BiOI compound according to claim 6. 1-x (OH) x , or the anion exchange membrane of claim 8 or 9.

Citation Information

Patent Citations

  • Bismuth-based catalyst for electrocatalytic CO2 reduction to form formic acid and preparation method and application thereof

    CN109518222A

  • Anion intercalation double-metal hydroxide adsorbent, preparation method and application thereof

    CN112871128A

  • Alkaline anion exchange membranes and methods of use thereof

    US20220370998A1